Model Theory of Reasoned Action with Digital Literacy as a Supporting Factor in Digital Driven Indonesian MSMEs - PANJAITAN, Andry Manodotua; SUDIBJO, Niko; MEILANI, Cahya Palupi (PT Keberlanjutan Strategis Indonesia, 2023)
This research aims to determine the influence of attitude toward behavior, subjective norms and digital technology literacy on intention to adopt digital technology, as well as its influence on digital technology use behavior in MSMEs that use technology in Indonesia. A total of 532 samples were used in this research by testing using SEM PLS analysis. The test results stated that the hypothesis raised was accepted. By having digital literacy, MSME owners or leaders can increase awareness of changes in market competition so they can formulate clear digital transformation goals in their business. By having digital literacy, MSME owners or leaders are able to use digital technology not only for marketing but can also be used to innovate and develop business.